2023
DOI: 10.1111/1365-2745.14096
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory dynamics drive grassland recovery from drought

Abstract: 1. Grasslands are expected to experience droughts of unprecedented frequency and magnitude in the future. Characterizing grassland responses and recovery from drought is therefore critical to predict the vulnerability of grassland ecosystems to climate change. Most previous studies have focused on ecosystem responses during drought while investigations of post-drought recovery are rare.Few studies have used functional traits, and in particular bud or clonal traits, to explore the mechanisms underlying grasslan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…of these two species, the greater heat tolerance conveyed by the C 4 photosynthetic pathway, and the low resilience of C 3 bunchgrasses to experimental warming and drying and modeled future conditions suggests a likely greater future dominance of P. jamseii and Sporobolus spp. relative to the C 3 bunchgrasses (Havrilla et al, 2022; Luo et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…of these two species, the greater heat tolerance conveyed by the C 4 photosynthetic pathway, and the low resilience of C 3 bunchgrasses to experimental warming and drying and modeled future conditions suggests a likely greater future dominance of P. jamseii and Sporobolus spp. relative to the C 3 bunchgrasses (Havrilla et al, 2022; Luo et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, ecosystem responses and sensitivity to drought can vary dramatically, and although fewer experiments have focussed on the recovery of ecosystem functioning post‐drought (Luo, Ma, et al., 2023), both large‐scale observations (Jiao et al., 2021; Li et al., 2023; Petrie et al., 2018; Schwalm et al., 2017; Wu et al., 2018) and past experiments suggest that there is quite significant variability in the recovery of ecosystems post‐drought (e.g. Stuart‐Haëntjens et al., 2018).…”
Section: Looking Forwardmentioning
confidence: 99%
“…Stuart‐Haëntjens et al., 2018). Some evidence suggests that drought resistance and recovery may be tightly coupled (Ingrisch et al., 2023), but experiments have also shown that rapid recovery can occur despite low drought resistance, with many mechanisms proposed (Correa‐Díaz et al., 2023; Griffin‐Nolan, Carroll, et al., 2018; Hoover et al., 2014; Luo, Ma, et al., 2023; Luo, Muraina, Griffin‐Nolan, Ma, et al., 2023; Stuart‐Haëntjens et al., 2018). Of greater concern is that some ecosystems may recover very slowly (if at all) to pre‐drought states when drought is extreme (Müller & Bahn, 2022; Smith, 2011a; Vilonen et al., 2022), Importantly, insufficient recovery post‐drought may exacerbate or ameliorate impacts of subsequent droughts.…”
Section: Looking Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants can alternatively tolerate drought‐induced lower tissue water content by reducing their tiller abundance and carbon allocation for growth and undergoing temporary above‐ground senescence (Dalgleish & Hartnett, 2006; Meng et al, 2022; Qian et al, 2023; Reichmann et al, 2013). Given that bud banks can withstand the extremes of drought better than above‐ground portions of plants (VanderWeide & Hartnett, 2015), the ability of below‐ground buds during drought determines the post‐drought recovery of perennial (Loydi & Collins, 2021; Luo, Ma, et al, 2023; Vesk & Westoby, 2004). Thus, when adequate soil moisture returns, perennial plants reduce below‐ground bud production and increase above‐ground tillers to maximize above‐ground productivity (Dalgleish & Hartnett, 2006).…”
Section: Introductionmentioning
confidence: 99%